Analisis SWOT Dalam Pengembangan Agrowisata di Desa Pelaga Kecamatan Petang Kabupaten Badung - Taman Sari; Ketut Selamet; Sri Purnami (Universitas Warmadewa, 2020)
Abstract-Plaga Village, located in Petang Subdistrict, is the regency of Badung Regency, Bali Province which has the most potential to be developed as an agrotourism object compared to other regions. The purpose of this study is to find out: (1) internal and external factors that hinder the development of agro-tourism in Pelaga Village; (2) internal and external efforts that can be made to develop sustainable tourism villages in Pelaga Village; and (3) stakeholder perceptions regarding the development of sustainable tourism villages in Pelaga Village.This research uses a qualitative approach. The research location was chosen purposively, with the consideration that the tourism resources in Pelaga Village are diverse, besides that, the regional development priority is agriculture so that it is possible to develop eco-friendly agro-tourism and ecotourism. Respondents in this research are stakeholders related to tourism development in Pelaga Village. Data collected through observation, in-depth interviews, and literature study. The collected data were analyzed descriptively qualitatively and supplemented by analysis of survey data (quantitative) for interpretation of results. The results of the analysis show that the internal factors that inhibit the development of agro-tourism in the village of Plaga are about the continuity of production results due to natural factors and soil fertility due to continuous cropping patterns on the same product, so that soil nutrients become reduced for the same crop products. Whereas on the other hand the quality of agricultural products, especially Asparagus products, has superior quality (it has even received the best recognition in ASEAN). Another factor that the variation of agricultural products seems slow in its development is because farmers are still reluctant to learn and experiment with new plants.Other inhibiting factors are the unavailability of comfort and adequate sanitation. Internally and externally, efforts that can be made as a form of promotion and at the same time can absorb agricultural products with certainty include the development of relationships or business networks on a continuous basis both through travel agents, hotels and restaurants. The strategic position of the village of Plaga agro-tourism in the evening district is in the hold and maintain position. The appropriate intensive strategies implemented are (1) market penetration strategies; (2) Product development strategy. Keywords: Agrotourism; CBT; internal factor; eksternal factor; tourism village; Abstraksi-Desa Plaga yang terletak di Kecamatan Petang merupakan daerah handalan Kabupaten Badung Provinsi Bali yang paling berpotensi untuk dikembangkan menjadi obyek agrowisata dibandingkan dengan wilayah lainnya. Tujuan penelitian ini adalah untuk mengetahui: (1) faktor internal dan faktor eksternal yang menghambat pengembangan agrowisata di Desa Pelaga; (2) upaya internal maupun eksternal yang dapat dilakukan untuk pengembangan desa wisata berkelanjutan di Desa Pelaga; dan (3) persepsi stakeholders terkait tentang pengembangan desa wisata berkelanjutan di Desa Pelaga. Penelitian ini menggunakan pendekatan kualitatif. Pemilihan lokasi penelitian dilakukan secara purposive, dengan pertimbangan bahwa sumber daya pariwisata di Desa Pelaga beraneka ragam, selain itu, prioritas pengembangan wilayah adalah pertanian sehingga memungkinkan dikembangkan agrowisata dan ekowisata yang bersifat ramah lingkungan. Responden pada penlitian ini adalah stakeholders yang terkait dengan pengembangan pariwisata di Desa Pelaga. Data dikumpulkan melalui observasi, wawancara mendalam, dan studi kepustakaan. Data yang telah terkumpul dianalisis secara deskriptif kualitatif dan dilengkapi analisis data survei (kuantitatif) untuk interpretasi hasil. Hasil analisis menunjukan bahwa dari faktor internal yang menghambat perkembangan agrowisata di Desa Plaga adalah perihal Kontinyuitas hasil produksi yang diakibatkan faktor alam maupun kesuburan tanah yang akibat pola tanam yang terus menerus pada produk yang sama, sehingga unsur hara tanah menjadi berkurang untuk produk tanaman yang sama. Padahal disisi lain kualitas produk hasil pertanian khususnya produk Asparagus telah memiliki kualitas unggul (bahkan telah mendapat pengakuan terbaik di Asean). Faktor lain bahwa variasi produk pertanian terkesan lambat dalam perkembangannya disebabkan petani masih enggan untuk belajar dan melakukan percobaan terhadap tanaman baru. Faktor penghambat lainnya belum tersedianya kenyamanan dan kebersihan sanitasi yang memadai. Secara internal maupun eksternal upaya yang dapat dilakukan sebagai bentuk promosi dan sekaligus dapat menyerap hasil pertanian secara pasti antara lain pengembangan relasi atau jaringan usaha secara kontinyu baik melalui biro perjalanan wisata, hotel dan restoran. Posisi strategik agrowisata Desa Plaga Kecamatan petang berada pada posisi Hold and maintain. Strategi intensif yang tepat diterapkan yaitu (1) strategi penetrasi pasar; (2) Strategi pengembangan produk. Kata Kunci: Agrowisata; CBT; faktor internal; faktor eksternal; desa wisata